Political Discourse Theory as an approach to the study of resistance organizations: reflections on the case of the emergence of Circuito Fora do Eixo in Brazil - Barcellos, Rebeca de Moraes Ribeiro de; Dellagnelo, Eloise Helena do Livramento (Organizações & Sociedade, 2014)
Considering Political Discourse Theory - PDT (Laclau, Mouffe, 1985) a theoretical alternative capable of assisting in understanding the processes of resistance experienced by counter-hegemonic organizations, which may illustrate alternative practices to organize, this study aimed to analyze the context of the emergence of an alternative experience in cultural context in Brazil- the Circuito Fora do Eixo. The study suggests that the concepts proposed by this theory, such as hegemony, dislocation, logic of equivalence, nodal point and empty signifier can help to understand the dynamics of emergence of this movement. Our discussions indicate that PDT assists in understanding the organizational context of resistance and counter-hegemonic organizations, whose approach is still deficient in the Organizational Studies due to lack of adequate theoretical support for their analysis.